The main character’s personality in the trilogy novel of Negeri 5 Menara, Ranah 3 Warna, dan Rantau 1 Muara written by Ahmad Fuadi: literature study of SMA - Ratna Dewi Kartikasari; Lasmi Hartati (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research is motivated by the interest of researcherto find out how the personality of the main characterscontained in the trilogy of novel Negeri 5 Menara, Ranah 3 Warna, Rantau 1 Muara by Ahmad Fuadi with literature psychology study. This research uses descriptive qualitative method used to describe personality of main charactertrilogy in these novels. The results showed that the personality of the main character in the trilogy novel as many as 18 personalities.In the novelNegeri5 Menara as many as 5 personalitieswith two personalitiestypeconsist ofphlegmatis (tough, consistent, diligence, empathy) and type choleris(courage). In the novel Ranah 3 Warna as many as 7 personalitieswith two personalitiestype gepasioner(hardworker, strong, confident)and type phlegmatis(intelligent, simple, caring,tough). While, in the novel Rantau 1 Muara as many as 6 personalitieswith three personalities type consist ofphlegmatis(diligent, consistent, care, tough),gepasioner(hard worker) and choleris(courage).Thus, it can be concluded that tough personality is more dominant because the personality is presented in the trilogy novel. It indicates that the main characters havetough personality in studying especially reaching for dreams. This research is implemented in SMAN 11 Kota Tangerang Selatan and it can be concluded that the student understand in analyzing the personality of the main character in the trilogy novel by Ahmad Fuadi.